Multipoint (in Time) Problem for One Class of Evolutionary Pseudodifferential Equations - Horodets’kyi, V. V.; Drin, Ya. M. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We establish the well-posed solvability of a nonlocal multipoint (in time) problem for the evolution equations with pseudodifferential operators of infinite order.